2004
DOI: 10.1097/01.brs.0000131417.93637.9d
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Adjacent Segment Degeneration After PLIF

Abstract: 1) There was no correlation between radiologic degeneration of cranial adjacent segment and clinical results. 2) Risk factors for postoperative radiologic degeneration could not be detected in terms of each preoperative radiologic factor. 3) Coexistence of horizontalization of the lamina at L3 and facet tropism at L3-L4 may be one of the risk factors for neurologic deterioration resulting from accelerated L3-L4 degenerative change after L4-L5 PLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
132
6
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(146 citation statements)
references
References 40 publications
3
132
6
5
Order By: Relevance
“…19 Adjacent segment degenerative changes and instability at the level immediately above single-segment fusion with clinical deterioration are shown in up to 90% of the cases. [20][21][22][23] The incidence of radiographic adjacent segment disease following fusion has been reported to be as high as 50% in the cervical spine and 70% in the lumbar spine at 10 years. However, the incidence of clinically relevant symptomatic adjacent segment disease is quite lower, estimated at 25% in the cervical spine and 36% in the lumbar spine at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…19 Adjacent segment degenerative changes and instability at the level immediately above single-segment fusion with clinical deterioration are shown in up to 90% of the cases. [20][21][22][23] The incidence of radiographic adjacent segment disease following fusion has been reported to be as high as 50% in the cervical spine and 70% in the lumbar spine at 10 years. However, the incidence of clinically relevant symptomatic adjacent segment disease is quite lower, estimated at 25% in the cervical spine and 36% in the lumbar spine at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to find risk factors for ASD in order to predict and prevent this condition, with numerous factors suspected as culprits including patient factors such as age, gender, or bone mineral density; anatomical predisposition of the lamina and facet joints; preoperative condition of the disc and facet joints; number of fused segments; type of fusion and instrumentation; and coronal or sagittal alignment [1,2,5,7,8,10,13,17,18,23,26,28]. Since Aota et al [2] indicated that the incidence of post-fusion instability at the adjacent segments was far higher in older ([55 years) than in younger patients, patient age has been regarded as a major risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the clinical implication of a radiologically demonstrated ASD is uncertain. Many authors have found no correlation between radiological ASD and clinical symptoms [15,21,22,26,30,31,35,44,46].…”
Section: Introductionmentioning
confidence: 99%